Changing patterns of lifelong learning a study in surgeon education - Boer, Piet de (AO Foundation, 2012)
Changing Patterns of Lifelong Learning is the culmination of an 18-month research project based on interviews with 147 surgeons throughout the world. The findings show the evolving picture of career pathways that have changed over time and which vary from country to country. The book proposes a new model for understanding how a surgeon progresses from stage to stage in his or her career and describes how different career stages are associated with differing needs and educational preferences. It also illustrates how the way surgeons learn has changed and gives insights into what the future of successful medical education might look like. Understanding how surgical careers develop is critical if educational offerings are to be precisely targeted at physician needs. This publication is essential reading for all those interested in the field of medical education, especially those with global aspirations.